Unveiling mycoviral diversity in Ophiocordyceps sinensis through transcriptome analyses - Kang, Qin; Zhang, Jihong; Chen, Fangzhou; Dong, Caihong; Qin, Qilian; Li, Xuan; Wang, Hongtuo; Zhang, Huan; Meng, Qian (Frontiers in Microbiology, 2024)
Ophiocordyceps sinensis, an entomopathogenic fungus, infects larvae from the Lepidoptera: Hepialidae family, forming the valuable Chinese cordyceps. Mycoviruses are widespread across major lineages of filamentous fungi, oomycetes, and yeasts and have the potential to influence fungal biology and ecology. This study aimed to detect mycovirus within O. sinensis by isolating double-stranded RNA from six stains for transcriptomic sequencing and analyzing publicly available transcriptome data from 13 O. sinensis representative samples. Our analysis revealed 13 mycoviruses, with nine reported for the first time in O. sinensis. These mycoviruses are distributed across five families—Partitiviridae, Mitoviridae, Narnaviridae, Botourmiaviridae, Deltaflexiviridae—and two unclassified lineages, Ormycovirus and Vivivirus. This study also revealed frequent coinfections within individual O. sinensis strains and dynamic shifts in viral composition during fungal development. These findings enhance our knowledge of mycovirus diversity within O. sinensis and provide new insights into their taxonomy.